Rangelands Atlas: an ambitious, first-of-its-kind inventory aimed at making rangelands a prominent part of policy discussions - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The Atlas is publicly available at www.rangelandsdata.org/atlas.